Matching into Plastic Surgery: Insights into the Data. Issue 5 (20th May 2022) - Sarac, Benjamin A.; Janis, Jeffrey E.
Abstract : Summary: Matching into plastic and reconstructive surgery residency, whether integrated or independent, is a competitive process. This article serves to examine, review, and summarize data published on both residency application processes. Through the results summarized, applicants should carefully review the objective and subjective factors used in evaluation to strategize how to make themselves as competitive as possible. Specifically, though, early review of the data presented may allow applicants time to focus on what modifiable factors still remain before their respective application seasons.